Changes Over a Decade in Anthropometry and Fitness of Elite Austrian Youth Soccer Players - Gonaus, Christoph; Birklbauer, Jürgen; Lindinger, Stefan J.; Stöggl, Thomas L.; Müller, Erich (Frontiers in Physiology, 2019)
Increases in physical (e.g., high-intensity running and sprinting), technical (e.g., passing rate), and tactical (e.g., player density) aspects made elite level soccer more challenging within the past years. The aim of the study was to evaluate whether these evolutions are also been reflected in changes in anthropometric and fitness characteristics between former (2002 to 2005) and current (2012 to 2015) elite Austrian youth development center (U13 to U14) and soccer academy (U15 to U18) players. A battery of anthropometric, general and soccer-specific fitness tests was conducted annually at the end of each year. Independent t-test and Cohen’s d (ES) were calculated to compare the two four-year periods (2530 vs. 2611 players) at each age group separately. Current players were significantly faster in 20 m sprint (ES = 0.26–0.50) and reaction test (ES = 0.15–0.39, except for U18), but less flexible at sit-and-reach (ES = -0.19 to -0.55), in all age categories. Whereas height (ES = 0.26–0.32), body mass (ES = 0.11–0.18) and countermovement jump (ES = 0.24–0.26) increased significantly at youth development center level, current academy players performed superior at shuttle sprint (ES = 0.21–0.59), hurdles agility run (ES = 0.24–0.49), and endurance run (ES = 0.11–0.20). These changes over time in speed, change-of-direction ability, lower-body power, coordination, and endurance were attributed to modern training approaches (e.g., modified games and change-of-direction drills) and modifications in selection politics (e.g., coaches favor speed and decision-making skills).